Analisis Wacana Kritis dalam Lirik Lagu “Indonesia” Karya Rhoma Irama Berdasarkan Teori Teun A. van Dijk - Fahrudin Fahrudin (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study discusses the importance of language and discourse in communication using the critical discourse analysis (AWK) of the Teun A. van Dijk model. The focus of the research is the lyrics of the Indonesian song by Rhoma Irama which is full of social criticism about inequality and the suffering of the people. This song was chosen because the lyrics reflect the social realities that occur in society and have strong ideological values. The research uses a qualitative descriptive method with the researcher as the main instrument. The primary data is in the form of song lyric texts, while secondary data is obtained from journals, scientific articles, and relevant online sources to strengthen the interpretation of the research. The analysis is carried out through two main aspects, namely the text aspect and the social context aspect. On the text aspect, the research examines macro, superstructure, and micro structures. The macro structure contains the theme of religious nationalism, which emphasizes the unity of the nation within the framework of moral values and religiosity. The structure of the superstructure shows a systematic pattern of lyrical presentation, starting from the depiction of social problems to the invitation to build collective consciousness. Meanwhile, the microstructure can be seen from the use of strong, emotional, and religious diction, thus strengthening the message of social criticism that is to be conveyed persuasively. In terms of social context, the results of the study show that Indonesian songs reflect the condition of a society that experiences domination of rulers and structural injustice. However, through its lyrics, the song also emphasizes the moral power of the people to drive social change, foster collective awareness, and voice resistance to ongoing injustice.